Contact lens including hydrogel coating and methods of forming contact lens having hydrogel coating

By forming a non-silicone hydrophilic coating with PAA or PMAA-based on the silicone hydrogel contact lens, the problem of poor wetting caused by partial hydrophobicity of silicone is solved, and the user comfort and coating stability are improved.

CN119547005APending Publication Date: 2025-02-28ARGOS VISION INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380014119.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-05-15
Filing Date
2023-07-23
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing silicon hydrogel contact lenses have poor wetting due to the hydrophobicity of the silicone part, which affects the user's comfort, and the surface treatment technology has challenges such as stability, consistency, robustness and biocompatibility.

Method used

Using a coating method, the contact lens is immersed in a first treatment solution containing PAA or PMAA and then immersed in a second treatment solution containing metal cations to form a stable non-silicon hydrophilic coating.

Benefits of technology

The lubricity, hydrophilic properties and water film rupture time of the contact lens are improved, the user's comfort is enhanced, and the coating remains stable and biocompatible over the life of the contact lens.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119547005A_ABST
    Figure CN119547005A_ABST
Patent Text Reader

Abstract

A method of coating a contact lens includes immersing the contact lens in a first treatment solution, and immersing the contact lens in a second treatment solution to create a coating on the contact lens. The first treatment solution comprises: (1) PAA or PMAA; and (2) an alcohol, water, or a mixture of said alcohol and water. The second treatment solution comprises an aqueous solution of: (1) only metal cations; or (2) a metal cation and an acid-containing copolymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to methods of forming hydrogel coatings on contact lenses and contact lenses made thereby. Background Art

[0002] The need for refractive correction in daily life is increasing. With increasingly advanced digital technology and increasing network-generated knowledge, people's reliance on ophthalmic devices (such as glasses and contact lenses for myopia and hyperopia) is also increasing. Contact lenses are one of the main refractive correction devices and are becoming more and more popular due to their effectiveness, convenience and aesthetics.

[0003] Soft contact lenses based on HEMA (polyhydroxyethyl methacrylate) have been used for decades due to their good wettability and user comfort. However, more and more users experience blurred vision, excessive tearing, itching and burning sensations during prolonged wear due to hypoxia or insufficient oxygen. Soft contact lenses based on silicone hydrogel (SiHy) have been popular since 1999 because the lens material provides better oxygen permeability.

[0004] Although silicone hydrogel contact lens formulations provide better oxygen permeability, they make the lenses more hydrophobic or poorly wettable due to the hydrophobicity of the silicone portion, which directly affects user comfort. In order to overcome the hydrophobicity of the silicone portion or make the surface of SiHy contact lenses wettable, various surface treatment technologies have been introduced since silicone-based contact lenses were launched on the market in 1999. These technologies include plasma coating, hydrophilic polymer casting coating, and surface coating of SiHy contact lenses. The main challenges of SiHy surface treatment are its stability, consistency, robustness, and biocompatibility. The durability of the coating throughout the life of the contact lens is extremely challenging. The coating of the contact lens loses its properties during the shelf life of the product. In addition, contact lens manufacturing requires automation for large-scale production, and any additional manufacturing process or changes to accommodate the surface treatment of the contact lens become capital intensive.

[0005] There is a need for an improved contact lens and method of making the same that reduces one or more problems associated with prior art contact lenses and methods of making the same. Summary of the invention

[0006] In one embodiment, a method of coating a contact lens is disclosed. In one step, the contact lens is immersed in a first treatment solution, the first treatment solution comprising: (1) PAA or PMAA; and (2) alcohol, water, or a mixture of alcohol and water. In a second step, the contact lens is immersed in a second treatment solution to produce a coating on the contact lens. The second treatment solution comprises an aqueous solution of: (1) metal cations alone; or (2) metal cations and a copolymer.

[0007] In another embodiment, a contact lens comprises a coating. The coating comprises: PAA or PMAA. The coating further comprises: (1) a metal cation only; or (2) a metal cation and a copolymer.

[0008] The scope of the present disclosure is defined solely by the appended claims and is not affected by the statements within this summary. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] The present disclosure may be better understood with reference to the following drawings and descriptions. The components in the drawings are not necessarily drawn to scale, emphasis instead being placed upon illustrating the principles of the present disclosure.

[0010] Figure 1 is a flow chart illustrating one embodiment of a method of forming a contact lens.

[0011] Figure 2 is a flow chart illustrating one embodiment of a method of coating a contact lens.

[0012] Figure 3 One embodiment of the chemical composition of PAA is shown.

[0013] Figure 4 One embodiment of the chemical composition of the copolymer is shown.

[0014] Figure 5 is to follow Figures 1 to 2 A side view of one embodiment of a contact lens made by the method of FIG.

[0015] Figure 6 Shows Figure 5 A chemical substance of one embodiment of a coating on the surface of / on the surface of a contact lens.

[0016] Figure 7 One embodiment of a table showing the weight percentages of various monomers in contact lens A is shown.

[0017] Figure 8 One embodiment of a table showing the weight percentages of various monomers in contact lens B is shown.

[0018] Fig. 9 shows the display follows Figures 1 to 2 Table of test results of contact lenses A (data A to D) made using different first, second and third treatment solutions and control contact lenses (data E) to which no treatment solution was applied. The test results show lubricity CCOF (critical coefficient of friction) data, lubricity (friction) data, WBUT wettability data, stability data and contact lens distortion data. The Mv (viscosity average molecular weight) of PAA is 450,000.

[0019] Fig.10 shows the display follows Figures 1 to 2 Table of test results (data F to J) of contact lens A made using different first, second and third processing solutions according to the method of the present invention. The test results show lubricity CCOF (critical coefficient of friction) data, lubricity (friction) data, WBUT wettability data, stability data and contact lens distortion data. The Mv (viscosity average molecular weight) of PAA is 450,000.

[0020] Fig.11 shows the display follows Figures 1 to 2 Table of test results (data K to M) of contact lenses A made using different first, second and third processing solutions according to the method of the present invention. The test results show lubricity CCOF (critical coefficient of friction) data, lubricity (friction) data, WBUT wettability data, stability data and contact lens distortion data. The Mv (viscosity average molecular weight) of PAA is 450,000.

[0021] Fig.12 shows the display follows Figures 1 to 2 Table of test results (data N to O) of contact lenses A made using different first, second and third processing solutions according to the method of the present invention. The test results show lubricity CCOF (critical coefficient of friction) data, lubricity (friction) data, WBUT wettability data, stability data and contact lens distortion data. The Mv (viscosity average molecular weight) of PAA is 450,000.

[0022] Fig.13 shows the display follows Figures 1 to 2 Table of test results (data P to Q) of contact lenses A made using different first, second and third processing solutions according to the method of the present invention. The test results show lubricity CCOF (critical coefficient of friction) data, lubricity (friction) data, WBUT wettability data, stability data and contact lens distortion data. The Mv (viscosity average molecular weight) of PAA is 450,000.

[0023] Fig.14 shows the display follows Figures 1 to 2 Table of test results of contact lenses B (data R to S) made using different first, second and third treatment solutions and control contact lenses (data T) to which no treatment solution was applied. The test results show lubricity CCOF (critical coefficient of friction) data, lubricity (friction) data, WBUT wettability data, stability data and contact lens distortion data. The Mv (viscosity average molecular weight) of PAA is 450,000.

[0024] Fig.15 shows the display follows Figures 1 to 2Table of test results (data U to V) of contact lenses A made using different first, second and third processing solutions according to the method of the present invention. The test results show lubricity CCOF (critical coefficient of friction) data, lubricity (friction) data, WBUT wettability data, stability data and contact lens distortion data. The Mv (viscosity average molecular weight) of PAA is 450,000. DETAILED DESCRIPTION

[0025] Figure 1 is a flow chart illustrating one embodiment of a method 10 of forming a contact lens. The contact lens may include a soft silicone contact lens.

[0026] Step 12 may include distributing the monomer mixture between the male and female portions of the mold.The monomer mixture may contain different materials.

[0027] In one embodiment, the monomer mixture may include TRIS, i.e., 3-methacryloxypropyl tris-(trimethylsiloxy) silane, CAS No. 17096-07-0, available from Gelest Inc (Cat No. SIM6487.6). In another embodiment, the monomer mixture may include mPDMS 700, i.e., monomethacryloxypropyl end-capped polydimethylsiloxane, CAS No. 146632-07-7, available from Gelest Inc (Cat No. MCS-M07). In yet another embodiment, the monomer mixture may include SIGMA, i.e., (3-methacryloxy-2-hydroxypropoxypropyl) methylbis(trimethylsiloxy) silane, CAS No. 69861-02-5, available from Gelest Inc (Cat No. SIM6481.15). In yet another embodiment, the monomer mixture may include HEMA, i.e., hydroxyethyl methacrylate, CAS No. 868-77-9, available from Sigma Aldrich Co. In another embodiment, the monomer mixture may include IBM, i.e., isobornyl methacrylate, CAS No. 7534-94-3, available from Sigma Aldrich Co. In another embodiment, the monomer mixture may include NVP, i.e., 1-vinyl-2-pyrrolidone, CAS No. 88-12-0, available from Sigma Aldrich Co. In yet another embodiment, the monomer mixture may include MAA, i.e., methacrylic acid, CAS No. 79-41-4, available from Sigma Aldrich Co. In yet another embodiment, the monomer mixture may include PVP(K90), i.e., polyvinylpyrrolidone K90, CAS No. 9003-39-8, available from Sigma Aldrich Co. In another embodiment, the monomer mixture may include EGDMA, i.e., ethylene glycol dimethacrylate, CAS No. 97-90-5, available from Sigma Aldrich Co. In another embodiment, the monomer mixture may include TEGDMA, i.e., triethylene glycol dimethacrylate, CAS No. 109-16-0, available from Sigma Aldrich Co. In yet another embodiment, the monomer mixture may include DMA, i.e., N,N-dimethylacrylamide, CAS No. 2680-03-7, available from Sigma Aldrich Co. In another embodiment, the monomer mixture may include AIBN (thermal initiator), azobisisobutyronitrile, CAS No. 78-67-1, available from Sigma Aldrich Co. In yet another embodiment, the monomer mixture may include nPA (n-propanol or 1-propanol), CAS No. 71-23-8, available from Sigma Aldrich Co.In yet another embodiment, the monomer mixture may include D30 (3,7-dimethyl-3-octanol), CAS No. 106-21-8, available from Sigma Aldrich Co. In another embodiment, the monomer mixture may include ME, i.e. 2-mercaptoethanol, CAS No. 60-24-2, available from Sigma Aldrich Co. In yet another embodiment, the monomer mixture may include PEGMA, i.e. poly(ethylene glycol methacrylate), CAS No. 25736-86-1, Mn 360, available from Sigma Aldrich Co. In another embodiment, the monomer mixture may include IrgaCure 819, i.e. phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, CAS No. 162881-26-7, available from Sigma Aldrich Co. In other embodiments, the monomer mixture may be different.

[0028] In one embodiment, the mold can be made using injection molding to form the convex mating portion and the concave mating portion of the mold. The mold can be made of a variety of materials, such as homopolymers or copolymers, including polypropylene, ethylene vinyl alcohol, polybutylene terephthalate, polystyrene and nylon. Due to the shrinkage consistency, the mold can remain dimensionally stable within two hours after manufacture. Nucleating agents can be used to accelerate the molding process. In other embodiments, the mold can be made using different materials, systems and methods.

[0029] Step 14 may include sealing the convex and concave portions of the mold with the monomer mixture disposed in the mold. Step 16 may include curing the monomer mixture in the convex and concave portions of the closed mold. Curing may utilize thermal energy, radiation, or other types of curing processes. In step 18, the convex and concave portions of the mold may be separated (i.e., demolded) to open the mold. In step 20, the contact lens formed in the convex and concave portions of the mold may be removed from the mold. This may be accomplished by mechanical dry stripping, by using a solution to float the contact lens from the mold, or by another removal process.

[0030] Figure 2 is a flow chart illustrating one embodiment of a method 30 for coating a contact lens. The contact lens may be coated using Figure 1In other embodiments, the contact lens can be formed using a different method. The contact lens can be a soft silicone contact lens. In other embodiments, the contact lens can be different. In step 32, the contact lens can be immersed in a first treatment solution. In one embodiment, the contact lens can be immersed in the first treatment solution for 1 minute to 60 minutes. Preferably, the contact lens is immersed in the first treatment solution for 5 minutes to 30 minutes. The immersion temperature and / or the temperature of the first treatment solution can be 5°C to 65°C. Preferably, the immersion temperature and / or the temperature of the first treatment solution is room temperature to 45°C. In other embodiments, the time the contact lens is immersed in the first treatment solution and the immersion temperature and / or the temperature of the first treatment solution can be different. If the solution is floated for the de-lensing step, the de-lensing step and the immersion in the first treatment solution can be combined into a single step.

[0031] In one embodiment, the first treatment solution may contain PAA (polyacrylic acid, CAS No. 9003-01-4) and alcohol, water, or a mixture of water and alcohol. PAA can be purchased from Sigma Aldrich Co. Figure 3 One embodiment of the chemical composition of PAA is shown. In other embodiments, the PAA may be different. In another embodiment, the first processing solution may contain PMAA (polymethacrylic acid, CAS No. 25086-62-8) and an alcohol, water, or a mixture of water and alcohol. PMAA can be purchased from SigmaAldrich Co. The first processing solution may have a molecular weight in the range of 100,000 to 4,000,000. Preferably, the molecular weight range is 400,000 to 1,500,000. The PAA solution is made by dissolving PAA in a water / alcohol mixture in a concentration range of 0.01% to 5%. Preferably, its concentration range is 0.05% to 2%. The PAA solution may have a pH in the range of 1 to 6. Preferably, the PAA solution has a pH in the range of 2 to 4. The alcohol may include IPA (isopropyl alcohol), nPA (n-propanol), ethanol or other swelling solvents that can swell the contact lens, such as propylene glycol monomethyl ether. The alcohol concentration range may be 0% to 100%. The alcohol concentration range is preferably 20% to 60%. The first treatment solution does not need to be heated or pressurized to achieve the surface modification effect. In other embodiments, the first treatment solution may be different.

[0032] The contact lens may be rinsed with water in step 34. In other embodiments, the contact lens may be rinsed with a different solution.

[0033] In step 36, the contact lens can be immersed in a second treatment solution to produce a coating on the contact lens. In one embodiment, the second treatment solution can include an aqueous solution containing only metal cations. In another embodiment, the second treatment solution can include an aqueous solution containing metal cations and a copolymer. In yet another embodiment, the second treatment solution can be different. The contact lens can be immersed in the second treatment solution for 1 minute to 60 minutes. Preferably, the contact lens is immersed in the second treatment solution for 5 minutes to 15 minutes. The immersion temperature of the second treatment solution can be a temperature of 5°C to 65°C. Preferably, the immersion temperature of the second treatment solution is a temperature of room temperature to 45°C. In other embodiments, the contact lens can be immersed in the second treatment solution for different amounts of time, and the immersion temperature and / or the second treatment solution can be different temperatures.

[0034] In one embodiment, the metal cation may include a cationic salt such as CaCl 2 In another embodiment, the metal cation may include a metal ion salt including a water-soluble chemical containing any of the following cations: Ca 2+ Mg 2+ , Ba 2+ 、Zn 2+ , Fe 3+ 、Ag + Or different cations. The metal cation may have a concentration range of 0.01% to 10%. Preferably, the metal cation may have a concentration range of 0.01% to 5%. Most preferably, the metal cation may have a concentration range of 0.01% to 2%. In other embodiments, the metal cation may be different.

[0035] The copolymer may have a concentration range of 0.01% to 10%. Preferably, the copolymer has a concentration range of 0.01% to 5%. Most preferably, the copolymer has a concentration range of 0.01% to 2%.

[0036] In one embodiment, the copolymer may include an acid-containing copolymer of acrylamide and acrylic acid, such as poly(acrylamide-co-acrylic acid) (80% / 20%), ie, polyAAm-co-AA, available from Sigma Aldrich, CAS No. 62649-23-4, with a molecular weight of 520,000. Figure 4One embodiment of the chemical composition of the copolymer is shown. In other embodiments, the copolymer may be different. In another embodiment, the copolymer may include an acid-containing copolymer poly(acrylamide-co-acrylic acid) (95% / 5%), which is made from a mixture of 9.5 grams of acrylamide, 0.5 grams of acrylic acid, and 0.5 grams of AIBN in 90 milliliters (ml) of water. The mixture can be cured at 100°C under nitrogen for 1 hour, and the resulting polymer can contain 10% water. In yet another embodiment, the copolymer may include an acid-containing copolymer poly(NVP-co-MAA) (90% / 10%), which is made from a mixture of 8.9 grams of NVP, 1 gram of MAA, 0.05 grams of ME, and 0.05 grams of AIBN in 40 ml of water. The mixture can be cured at 80°C under nitrogen for 4 hours, and the resulting polymer can have 20% water. In yet another embodiment, the copolymer may include an acid-containing copolymer poly(PEGMA-co-MAA) (90% / 10%) made from a mixture of 8.9 grams of PEGMA, 1 gram of MAA, 0.05 grams of ME, and 0.05 grams of AIBN in 40 ml of water. The mixture may be cured at 80° C. under nitrogen for 4 hours, and the resulting polymer may have 20% water. In yet other embodiments, the copolymer may be different.

[0037] The contact lens may be rinsed with water in step 38. In other embodiments, the contact lens may be rinsed with a different solution.

[0038] In optional step 40, the contact lens can be immersed in a third treatment solution. The third treatment solution can include an aqueous solution of only metal cations. In other embodiments, the third treatment solution can be different. The contact lens can then be rinsed with water. In other embodiments, the contact lens can then be rinsed with a different solution.

[0039] The contact lens may be immersed in the third treatment solution for 1 minute to 60 minutes. Preferably, the contact lens is immersed in the third treatment solution for 5 minutes to 15 minutes. The immersion temperature and / or the third treatment solution may be a temperature of 5° C. to 65° C. Preferably, the immersion temperature and / or the third treatment solution may be a temperature of room temperature to 45° C. In other embodiments, the contact lens may be immersed in the third treatment solution for different amounts of time, and the immersion temperature and / or the third treatment solution may be different temperatures.

[0040] In one embodiment, the metal cation may comprise a cationic salt such as CaCl 2 In another embodiment, the metal cation may include a metal ion salt including a water-soluble chemical containing any of the following cations: Ca 2+ Mg 2+ , Ba 2+ 、Zn2+ , Fe 3+ 、Ag + Or different cations. The metal cation may have a concentration range of 0.01% to 10%. Preferably, the metal cation may have a concentration range of 0.01% to 5%. Most preferably, the metal cation may have a concentration range of 0.01% to 2%. In other embodiments, the metal cation may be different.

[0041] The contact lens may be rinsed with water in optional step 42. In other embodiments, the contact lens may be rinsed with a different solution.

[0042] In step 44, the contact lens can be placed in a container with the buffer solution, and then the container can be sealed. In one embodiment, the container can include a glass vial. In another embodiment, the container can include a plastic blister. In other embodiments, the container can be different.

[0043] In one embodiment, the buffer solution may include PBS (phosphate buffered saline). PBS may include PBS tablets purchased from RPI Research Products International. One tablet may be dissolved in 100 ml of water to obtain 11.9 mM sodium phosphate with a pH of 7.4. In another embodiment, the buffer solution may include TBS (Tris buffered saline). TBS may include Trizma base (tris (hydroxymethyl) aminomethane), CAS No. 77-86-1, purchased from Sigma Aldrich. Buffered saline may be prepared by mixing 6.05 grams of Trizma base and 8.76 grams of sodium chloride in 1 liter of water, and then adjusting the pH to 7.4 with 1M hydrochloric acid (HCl). The resulting buffer solution may include 50 mM tris (hydroxymethyl) aminomethane. In yet another embodiment, TBS may include TBS-NaAc (Tris buffer-sodium acetate without chloride ions for silver nitrate treatment only). TBS may include Trizma base (tris (hydroxymethyl) aminomethane), CAS No. 77-86-1, purchased from Sigma Aldrich. Buffered saline can be prepared by mixing 6.05 grams of Trizma base and 8.76 grams of sodium acetate in 1 liter of water, and then adjusting the pH to 7.4 with 1 M acetic acid (HAc). The resulting buffer solution can contain 50 mM tris (hydroxymethyl) aminomethane. In other embodiments, the buffer solution can be different.

[0044] In step 46, the sealed contact lens can be autoclaved. The contact lens can be autoclaved at 121° C. for 40 minutes. In other embodiments, the contact lens can be autoclaved at different temperatures for different amounts of time. In still other embodiments, different processes can be used for the sealed contact lens.

[0045] Figure 5 is to follow Figures 1 to 2 A side view of one embodiment of a contact lens 50 made by the method of FIG. Figure 6 Shown in Figure 5 In one embodiment of the surface 54 of the contact lens 50 / the coating 52 on the surface 54 is Ca 2+ The coating chemistry of the ionic hydrogel formed by cross-linking PAA and poly (AAm-co-AA). The coating 52 may include Figures 1 to 2 Alternatively, the non-silicone stabilized ionic hydrogel coating 52 may comprise polymethacrylic acid (PMAA), poly(NVP-co-MAA), poly(PEGMA-co-MAA), 2 + Cationic salts (such as CaCl 2 or ZnCl 2 ) and 1 + Cationic salts (such as AgNO 3 ). In other embodiments, the chemistry of the non-silicone stabilized ionic hydrogel coating 52 may be different.

[0046] The coating 52 on the contact lens 50 (which may include a soft silicone contact lens) may provide improved lubricity, improved hydrophilic properties, and improved water breakup time (WBUT) to improve user comfort. The coating 52 may have a CCOF (critical coefficient of friction) lubricity in the range of 0.02 to 0.06, may have a friction lubricity in the range of 3 to 5, and may have a water breakup time (WBUT) greater than 10 seconds. Figure 1 and Figure 2 The coating 52 can form a metal ion gel and behave as a polyelectrolyte gel. The coating 52 can include PAA or PMAA and multivalent cations (such as Ca 2+ Mg 2+ , Ba 2+ 、Zn 2+ , Fe 3+ and Fe 2+) can form a non-silicone stable ionic hydrogel coating that can form a cross-linked hydrogel network prior to additional heating or autoclaving. Monovalent cations (such as Ag+) can form insoluble hydrogels with PAA or PMAA and can provide antimicrobial applications for contact lenses 50. In other embodiments, various metal cations can form insoluble hydrogels with PAA, PMAA or other compounds. Once placed in a buffer solution, the contact lens 50 can be stored for several years without the coating 52 changing its composition.

[0047] In other embodiments, one or more steps of method 10 may differ in substance or order, may not be followed, or one or more additional steps may be added to method 10 in any order.

[0048] Figure 7 One embodiment of a table showing the weight percentages of various monomers in contact lens A is shown. Figure 8 One embodiment of a table showing the weight percentages of various monomers in contact lens B is shown. Contact lenses A and B include soft silicone contact lenses. For contact lens A, Dk is 60-70 bar and the water content is 55%. The monomer mixture is dispensed into the cavities of convex and concave contact lens molds and cured in nitrogen at 60°C for 30 min, 80°C for 30 min, and then at 100°C for 3 hours. The dried contact lenses are easily removed from the convex and concave molds. For contact lens B, Dk is 133-140 bar and the water content is 35%. The monomer mixture is dispensed into the cavities of male and female contact lens molds and cured with radiation, such as ultraviolet light (3 mW / cm 2 ) for 90 min. The preferred method of de-lensing is by solution flotation. The solution is made of 50% water and 50% isopropanol.

[0049] Figures 9 to 13 and 15 show the display as detailed above to follow Figures 1 to 2 Table of test results of contact lenses A (data A to D, F to Q and U to V) made using different first, second and third treatment solutions and control contact lenses (data E) to which no treatment solution was applied. The test results show lubricity CCOF (critical coefficient of friction) data, lubricity (friction) data, WBUT wettability data, stability data and contact lens distortion data. Fig.15 Additionally shown are results showing two years of aging of contact lenses A in different buffer solutions at room temperature (about 22°C). Figures 9 to 13 The Mv (viscosity average molecular weight) of PAA used in and 15 was 450,000.

[0050] Fig.14shows the display as detailed above to follow Figures 1 to 2 Table of test results of contact lenses B (data R to S) made using different first, second and third treatment solutions and control contact lenses (data T) to which no treatment solution was applied. The test results show lubricity CCOF (critical coefficient of friction) data, lubricity (friction) data, WBUT wettability data, stability data and contact lens distortion data. Fig.14 The Mv (viscosity average molecular weight) of PAA used in was 450,000.

[0051] for Figures 9 to 15 , CCOF lubricity data includes the critical coefficient of friction (CCOF) based on the inclined plane method (sliding angle, reference ASTM D4918-97). For this lubricity data, the apparatus includes a PBS buffer tank, a borosilicate glass plate located in the tank, and a 0.79 gram stainless steel weight. In order to measure, a contact lens is placed under the stainless steel weight on the glass surface. The entire tank is filled with PBS buffer. The angle of the tilted glass plane is adjusted and measured with a digital inclinometer. When the slope of the glass plane exceeds a certain angle (critical angle), the stainless steel weight begins to move and slides to one side of the tank together with the contact lens. The tangent of the critical angle is the CCOF (critical coefficient of friction).

[0052] for Figures 9 to 15 The friction lubricity data is obtained by placing various contact lenses on the palm of the tester's hand and rubbing the contact lenses with the tester's fingertips. The measurement results are 0 for great resistance, 1 for resistance, 2 for slight resistance, 3 for slight slippery feeling, 4 for relatively slippery, and 5 for very slippery.

[0053] for Figures 9 to 15 , WBUT wettability data is obtained by removing the contact lens from the PBS solution and shaking the contact lens to remove excess water. The time (in seconds) required to observe a dry area greater than half of the total area of ​​the lens. The longer the WBUT measurement time, the better the wettability of the contact lens. Very wettable contact lenses typically have WBUT measurements of more than 15 seconds.

[0054] for Figures 9 to 15 Stability data was obtained by autoclaving contact lenses three times (3x) and then examining the changes in friction lubricity and diameter.

[0055] for Figures 9 to 15 , distortion data is obtained by observing whether the coating causes the contact lens to deform.

[0056] refer to Fig. 9It is noteworthy that in contact lens A, it was observed that the IPA concentration in the first treatment affected the lens lubricity after autoclaving. The concentration of IPA was 10% to 60%, preferably 30% to 50%. Other substitutes for IPA, such as nPA, propylene glycol monomethyl ether, can also be used.

[0057] refer to Fig.10 , noting that in contact lens A, PMAA was as effective as PAA in the first treatment. In the second treatment, copolymers polyAAm-co-AA (5% AA), polyNVP-co-MAA, and polyPEGMA-co-MAA provided comparable Fig. 9 The copolymer may have acrylic acid functional groups.

[0058] refer to Fig.11 , it is noted that in contact lens A, other cations (such as zinc (Zn 2+ ) and silver (Ag + )) also provides lubricity. However, for AgNO 3 The buffer solution (silver nitrate) was Tris-NaAc buffered saline (in the Materials section), specifically designed to avoid precipitation of silver chloride in the buffer solution.

[0059] refer to Fig.12 , note that in contact lens A, sample O has additional CaCl 2 The purpose of the third treatment is to complex any unbound PAA in the coating.

[0060] refer to Fig.13 , note that in contact lens A, sample Q does not contain the copolymer but still provides a stable coating for the product.

[0061] refer to Fig.14 , note that in contact lens B, we observed a similar surface modification effect, but the effect was less severe compared to contact lens A.

[0062] refer to Fig.15 , it was noted that in contact lens A after aging for 2 years at room temperature (about 22° C.), the lubrication stability of the contact lens was better maintained in TBS (Tris buffered saline) than in PBS (phosphate buffered saline).

[0063] Figures 9 to 15 The test results shown in the application Figures 1 to 2 The method provides unexpected key results for manufacturing contact lenses with excellent lubricity, WBUT, stability and distortion results.

[0064] One or more embodiments of the present disclosure can provide an efficient and inexpensive method to produce an effective and durable non-silicone hydrophilic coating on the surface of a SiHy contact lens using a procedure compatible with conventional contact lens manufacturing processes prior to the autoclave sterilization step. The coating process can be adapted to the extraction / hydration step of the existing contact lens manufacturing process. The methods of the present disclosure can produce coatings on contact lenses without the need for further chemical reactions at elevated temperatures or conventional autoclave sterilization. This can save a significant amount of time and cost during the manufacture of contact lenses. In addition, the coatings on contact lenses manufactured using these methods can be stable, consistent, robust, biocompatible and durable over the life of the contact lens without losing their properties.

[0065] The abstract is provided to allow the reader to quickly ascertain the nature of the technical disclosure. It should be understood that the abstract will not be used to interpret or limit the scope or meaning of the claims. In addition, in the foregoing detailed description, it can be seen that various features are grouped together in various embodiments for the purpose of making the text of the disclosure flow smoothly. This method of the present disclosure should not be interpreted as reflecting the following intention: the claimed embodiments require more features than the features explicitly recited in each claim. Rather, as reflected in the following claims, the inventive subject matter lies in less than all the features of a single disclosed embodiment. Therefore, the following claims are hereby incorporated into the specific embodiments, with each claim independently serving as a separately claimed subject matter.

[0066] Although specific aspects of the subject matter described herein have been shown and described, it will be apparent to those skilled in the art that changes and modifications may be made based on the teachings herein without departing from the subject matter described herein and its broader aspects, and the appended claims are intended to cover within their scope all such changes and modifications that are within the true scope of the subject matter described herein. In addition, it should be understood that the present disclosure is defined by the appended claims. Therefore, the present disclosure is not limited except in accordance with the appended claims and their equivalents.

Claims

1. A method of coating a contact lens, the method comprising: immersing the contact lens in a first treatment solution comprising: (1) polyacrylic acid (PAA) or polymethacrylic acid (PMAA); and (2) alcohol, water, or a mixture of the alcohol and water; and The contact lens is immersed in a second treatment solution to produce a coating on the contact lens, the second treatment solution comprising an aqueous solution of: (1) metal cations alone; or (2) metal cations and a copolymer.

2. The method of claim 1, wherein immersing the contact lens in the first treatment solution comprises immersing the contact lens in the polyacrylic acid (PAA) and the alcohol, water, or a mixture of the alcohol and water.

3. The method of claim 1, wherein immersing the contact lens in the first treatment solution comprises immersing the contact lens in the polymethacrylic acid (PMAA) and the alcohol, water, or a mixture of the alcohol and water.

4. The method of claim 1, further comprising rinsing the contact lens in water after immersing the contact lens in the first treatment solution and before immersing the contact lens in the second treatment solution.

5. The method of claim 1, wherein immersing the contact lens in the second treatment solution comprises immersing the contact lens in the aqueous solution of only metal cations.

6. The method of claim 5, wherein the only metal cations comprise: Ca 2+ , Mg 2+ , B.A. 2+ , Zn 2+ , Fe 3+ Some Ag + .

7. The method of claim 1, wherein immersing the contact lens in the second treatment solution comprises immersing the contact lens in an aqueous solution of the metal cation and the copolymer.

8. The method of claim 7, wherein the metal cation comprises: Ca 2+ , Mg 2+ , B.A. 2+ , Zn 2+ , Fe 3+ Some Ag + .

9. The method of claim 7, wherein the copolymer comprises an acid-containing copolymer comprising: Poly(acrylamide-co-acrylic acid), poly(NVP-co-MAA), or poly(PEGMA-co-MAA).

10. The method of claim 1, further comprising rinsing the contact lens with water after immersing the contact lens in the second treatment solution.

11. The method of claim 1, further comprising immersing the contact lens in a third treatment solution comprising an aqueous solution of only the metal cations, and then rinsing the contact lens with water.

12. The method of claim 11, wherein the only metal cations comprise: Ca 2+ , Mg 2+ , B.A. 2+ , Zn 2+ , Fe 3+ Some Ag + .

13. The method of claim 1, further comprising placing the contact lens in a container having a buffer solution, and sealing the contact lens in the container having the buffer solution.

14. The method of claim 13, wherein the buffer solution comprises PBS (phosphate buffered saline) or TBS (Tris buffered saline).

15. The method of claim 13, further comprising autoclaving the sealed contact lens in the container with the buffer solution.

16. The method of claim 15, further comprising maintaining the contact lens in the container within the buffer solution for several years while the coating retains its properties and composition.

17. The method of claim 1, further comprising forming a cross-linked hydrogel network on the contact lens prior to autoclaving.

18. The method of claim 1, further comprising the coating comprising a metal ion gel that functions as a polyelectrolyte gel.

19. The method of claim 1 further comprising applying a modified coating to the surface of the contact lens.

20. The method of claim 1, further comprising a coating having a CCOF (critical coefficient of friction) lubricity in the range of 0.02 to 0.

06.

21. The method of claim 1, further comprising a coating having a water breakup time greater than 10 seconds.

22. The method of claim 1, further comprising a coating having antimicrobial properties.

23. The method of claim 22, further comprising a coating comprising Ag+.

24. The method of claim 1, wherein the contact lens comprises a soft contact lens.

25. The method of claim 24, wherein the soft contact lens comprises a silicone contact lens.

26. A contact lens, comprising: A coating comprising (1) Polyacrylic acid (PAA) or polymethacrylic acid (PMAA); as well as (1) metal cation only; or (2) metal cation and copolymer.

27. The contact lens of claim 26, wherein the coating comprises polyacrylic acid (PAA).

28. The contact lens of claim 26, wherein the coating comprises polymethacrylic acid (PMAA).

29. The contact lens of claim 26, wherein the coating comprises only the metal cations.

30. The contact lens of claim 29, wherein the only metal cations comprise: Ca 2+ , Mg 2+ , B.A. 2+ , Zn 2+ , Fe 3+ Some Ag + .

31. The contact lens of claim 26, wherein the coating comprises the metal cation and the copolymer.

32. The contact lens of claim 31 , wherein the metal cation comprises: Ca 2+ , Mg 2+ , B.A. 2+ , Zn 2+ , Fe 3+ Some Ag + .

33. The contact lens of claim 31 , wherein the copolymer comprises: Poly(acrylamide-co-acrylic acid), poly(NVP-co-MAA), or poly(PEGMA-co-MAA).

34. The contact lens of claim 26, wherein the coating comprises a cross-linked hydrogel network.

35. The contact lens of claim 26, wherein the coating comprises a metal ion gel that functions as a polyelectrolyte gel.

36. The contact lens of claim 26, wherein the coating has a CCOF (critical coefficient of friction) lubricity in the range of 0.02 to 0.

06.

37. The contact lens of claim 26, wherein the coating has a water film breakup time greater than 10 seconds.

38. The contact lens of claim 26, wherein the coating has antimicrobial properties.

39. The contact lens of claim 38, wherein the coating comprises Ag+.

40. The contact lens of claim 26, wherein the contact lens comprises a soft contact lens.

41. The contact lens of claim 40, wherein the soft contact lens comprises a silicone contact lens.